2020
DOI: 10.1371/journal.pone.0227649
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium deposition in the brain of dogs after multiple intravenous administrations of linear gadolinium based contrast agents

Abstract: Objective To determine the effect of a linear gadolinium-based contrast agent (GBCA) on the signal intensity (SI) of the deep cerebellar nuclei (DCN) in a retrospective clinical study on dogs after multiple magnetic resonance (MR) examinations with intravenous injections of gadodiamide and LA-ICP-MS analysis of a canine cerebellum after gadodiamide administration. Animals 15 client-owned dogs of different breeds and additionally 1 research beagle dog cadaver. Procedures In the retrospective study part, 15 dogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The contrast agent gadolinium is used more frequently in dogs than in humans, likely because there are concerns about gadolinium toxicity, deposition and retention in humans within the brain and bones, as well as possible deleterious effects of gadolinium on renal function in humans [54 , 55] . There is limited data in dogs, but a recent small retrospective MRI study indicated there was no visible increased SI in the brain after multiple gadolinium exposures [56] . Most studies of gadolinium-based contrast agents (GBCAs) in animals have been performed in rodents, which confirm similar deposition of gadolinium to humans in the brain, bones and kidneys [57] , [58] , [59] .…”
Section: Discussionmentioning
confidence: 99%
“…The contrast agent gadolinium is used more frequently in dogs than in humans, likely because there are concerns about gadolinium toxicity, deposition and retention in humans within the brain and bones, as well as possible deleterious effects of gadolinium on renal function in humans [54 , 55] . There is limited data in dogs, but a recent small retrospective MRI study indicated there was no visible increased SI in the brain after multiple gadolinium exposures [56] . Most studies of gadolinium-based contrast agents (GBCAs) in animals have been performed in rodents, which confirm similar deposition of gadolinium to humans in the brain, bones and kidneys [57] , [58] , [59] .…”
Section: Discussionmentioning
confidence: 99%
“…However, macrocyclic agents resulted in less hyperintensity with a T1 signal increase compared to pre-contrast images of 20% and 7% for gadobutrol and gadoteridol, respectively (McDonald et al 2017b ). However with a more clinically relevant dose, dogs administered 2–3 doses of gadodiamide had no differences in hyperintensity in the DCN or pons on unenhanced T1-weighted MR images, compared with pre-contrast images (Richter et al 2020 ). The dentate nucleus and globus pallidus, the brain regions which for most studies appear to show the highest T1 hyperintensity are also areas where iron, copper and zinc concentrations are high, suggesting possible transmetalation by competition of the chelate for these metals, resulting in Gd 3+ dissociation and subsequent retention (Lauffer 1987 ; Cacheris et al 1990 ; Caravan et al 1999 ; Rasschaert et al 2018a ; Minaeva et al 2020 ).…”
Section: Gadolinium Distribution In Humans and Animalsmentioning
confidence: 99%
“…LA-ICP-MS also demonstrated that Gd may be deposited in various other organs including the brain. 275 Similarly, quantitative LA-ICP-MS was employed to study the accumulation of Pt-based cytostatic agents in the testis, kidney and cochlea, liver, kidney spleen, and muscle, which is of interest to understand side effects including oto-and nephrotoxicity. 145,276,277 Halbach et al 220 examined the uptake of the Br-containing acetylcholinesterase inhibitor, Naled, in zebrafish embryos and found 280-fold enrichment.…”
Section: Exposure Sciencementioning
confidence: 99%
“…LA-ICP-MS/MS was further employed to correlate the levels of Gd with endogenous elements which provided evidence that the pathogenesis of nephrogenic systemic fibrosis was linked to the generation of insoluble Gd/Ca phosphate deposits (Figure ). LA-ICP-MS also demonstrated that Gd may be deposited in various other organs including the brain . Similarly, quantitative LA-ICP-MS was employed to study the accumulation of Pt-based cytostatic agents in the testis, kidney and cochlea, liver, kidney spleen, and muscle, which is of interest to understand side effects including oto- and nephrotoxicity. ,, Halbach et al examined the uptake of the Br-containing acetylcholinesterase inhibitor, Naled, in zebrafish embryos and found 280-fold enrichment.…”
Section: Applicationsmentioning
confidence: 99%